K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 11 2016

Giải:

Ta có:

\(x+8⋮x+1\)

\(\Rightarrow\left(x+1\right)+7⋮x+1\)

\(\Rightarrow7⋮x+1\)

\(\Rightarrow x+1\in\left\{1;-1;7;-7\right\}\)

+) \(x+1=1\Rightarrow x=0\)

+) \(x+1=-1\Rightarrow x=-2\)

+) \(x+1=7\Rightarrow x=6\)

+) \(x+1=-7\Rightarrow x=-8\)

Vậy \(x\in\left\{0;-2;6;-8\right\}\)

23 tháng 11 2016

\(\frac{x+8}{x+1}=\frac{x+7+1}{x+1}=\frac{x+1}{x+1}+\frac{7}{x+1}\)

\(\Rightarrow x+1\in\text{Ư}\left(7\right)=\left\{1;7;-1;-7\right\}\)

\(\Rightarrow x\in\left\{0;6;-2;-8\right\}\)

23 tháng 11 2016

\(\frac{x+4}{x}=\frac{x}{x}+\frac{4}{x}\)

\(\Rightarrow x\in\text{Ư}\left(4\right)=\left\{1;2;4;-1;-2;-4\right\}\)

23 tháng 11 2016

Ta có :

\(x+4⋮x\)

=> \(x+4-x⋮x\)

=> \(4⋮x\)

=> \(x\inƯ_4\)

=> x\(\in\left\{1;2;4;-1;-2;-4\right\}\)

23 tháng 11 2016

\(\frac{x+5}{x+1}=\frac{x+4+1}{x+1}=\frac{x+1}{x+1}+\frac{4}{x+1}\)

\(\Rightarrow x+1\in\text{Ư}\left(4\right)=\left\{1;2;4;-1;-2;-4\right\}\)

\(\Rightarrow x\in\left\{0;1;3;-2;-3;-5\right\}\)

23 tháng 11 2016

x+5\(⋮\)x+1

x+1+4\(⋮\)x+1

Vì x+1\(⋮\)x+1

Buộc 4\(⋮\)x+1=>x+1ϵƯ(4)={1;2;4}

Với x+1=1=>x=0

x+1=2=>x=1

x+1=4=>x=3

Vậy xϵ{0;1;3}

23 tháng 11 2016

\(\frac{x+1+3}{x+1}=\frac{x+1}{x+1}+\frac{3}{x+1}\)

\(\Rightarrow x+1\in\text{Ư}\left(3\right)=\left\{1;-1;3;-3\right\}\)

\(\Rightarrow x\in\left\{0;-2;2;-4\right\}\)

23 tháng 11 2016

Ta có :

\(x+1+3⋮x+1\)

=> \(x+1+3-\left(x+1\right)⋮x+1\)

=> \(3⋮x+1\)

=> \(x+1\inƯ_3\)

=> \(x+1\in\left\{1;3;-1;-3\right\}\)

=> \(x\in\left\{0;2;-2;-4\right\}\)

23 tháng 11 2016

Ta có :

\(9⋮2x+1\)

=> \(2x+1\inƯ_9\)

=> \(2x+1\in\left\{1;3;9\right\}\)

=> \(2x\in\left\{0;2;8\right\}\)

=> \(x\in\left\{0;1;4\right\}\)

Vậy \(x\in\left\{0;1;4\right\}\)

a: =-1/5x^5y^2

b: =-9/7xy^3

c: =7/12xy^2z

d: =2x^4

e: =3/4x^5y

f: =11x^2y^5+x^6

a: =-4xyz^2

b: =-9x^2y

c: =16x^2y^2

d: =1/6x^2y^3

e: =13/6x^3y^2

f: =7/12x^4y

30 tháng 5 2023

a) -xyz² - 3xz.yz

= -xyz² - 3xyz²

= -4xyz²

b) -8x²y - x.(xy)

= -8x²y - x²y

= -9x²y

c) 4xy².x - (-12x²y²)

= 4x²y² + 12x²y²

= 16x²y²

d) 1/2 x²y³ - 1/3 x²y.y²

= 1/2 x²y³ - 1/3 x²y³

= 1/6 x²y³

e) 3xy(x²y) - 5/6 x³y²

= 3x³y² - 5/6 x³y²

= 13/6 x³y²

f) 3/4 x⁴y - 1/6 xy.x³

= 3/4 x⁴y - 1/6 x⁴y

= 7/12 x⁴y

7 tháng 12 2015

\(\left(x+\frac{1}{2}\right)+\left(x+\frac{1}{4}\right)+\left(x+\frac{1}{8}\right)+\left(x+\frac{1}{16}\right)=1\)

\(\Leftrightarrow4\text{x}+\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}=1\)

\(\Leftrightarrow4\text{x}+\frac{15}{16}=1\)

\(\Leftrightarrow4\text{x}=1-\frac{15}{16}\)

\(\Leftrightarrow4\text{x}=\frac{1}{16}\)

\(\Leftrightarrow x=\frac{1}{16}:4=\frac{1}{64}\)

7 tháng 12 2015

(x+1/2)+(x+1/4)+(x+1/8)+(x+16)=1

(x.x.x.x)+(1/2+1/4+1/8+1/16=1

4x+(1/2+1/4+1/8+1/16)=1

4x+(8/16+4/16+2/16+1/16)=1

4x+15/16=1

4x=1-15/16

4x=1/16

x=1/16:4

=>x=1/64

tick cho mk nha bạn

30 tháng 6 2017

\(\left(x+\frac{1}{2}\right)+\left(x+\frac{1}{4}\right)+\left(x+\frac{1}{8}\right)+\left(x+\frac{1}{16}\right)=1\)

\(\left(x+x+x+x\right)+\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}\right)=1\)

\(4x+\left(1+\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}\right)=1\)

\(4x+\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{8}+\frac{1}{8}-\frac{1}{16}\right)=1\)

\(4x+\left(1-\frac{1}{16}\right)=1\)

\(4x+\frac{15}{16}=1\)

\(4x=\frac{1}{16}\)

\(\Rightarrow x=\frac{1}{64}\)

30 tháng 6 2017

\(\left(x+\frac{1}{2}\right)+\left(x+\frac{1}{4}\right)+\left(x+\frac{1}{8}\right)+\left(x+\frac{1}{16}\right)=1\)

\(\left(x+x+x+x\right)+\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}\right)=1\)

\(4x+\frac{15}{16}=1\)

\(4x=\frac{1}{16}\)

\(x=\frac{1}{16}\div4\)

\(x=\frac{1}{64}\)

Vậy ...